2010
DOI: 10.1117/1.3406386
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quantitative image analysis criteria for the high-resolution microendoscopic detection of neoplasia in Barrett’s esophagus

Abstract: Abstract. Early detection of neoplasia in patients with Barrett's esophagus is essential to improve outcomes. The aim of this ex vivo study was to evaluate the ability of high-resolution microendoscopic imaging and quantitative image analysis to identify neoplastic lesions in patients with Barrett's esophagus. Nine patients with pathologically confirmed Barrett's esophagus underwent endoscopic examination with biopsies or endoscopic mucosal resection. Resected fresh tissue was imaged with fiber bundle microend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 22 publications
2
76
0
Order By: Relevance
“…Moreover, this dual-scale platform can be adapted to measure other molecular targets that have been used in the gastrointestinal tract with similar excitation and emission properties, 30 such as 2-NBDG or other targeted fluorescence contrast agents. 31,32 Furthermore, the signal associated with these fluorescent contrast agents can be quantified and used to aid in subjective image interpretation, 26,30 thereby further increasing its potential as a surveillance tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this dual-scale platform can be adapted to measure other molecular targets that have been used in the gastrointestinal tract with similar excitation and emission properties, 30 such as 2-NBDG or other targeted fluorescence contrast agents. 31,32 Furthermore, the signal associated with these fluorescent contrast agents can be quantified and used to aid in subjective image interpretation, 26,30 thereby further increasing its potential as a surveillance tool.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that these features can be consistently identified in HRME images and correlate with the appearance observed in H&E stained histologic sections. [19][20][21] Moreover, image processing algorithms have been developed for quantitative analysis of digital HRME images; initial pilot studies show high sensitivity and specificity for identifying neoplastic lesions, 26 suggesting the potential to use HRME imaging together with algorithmassisted identification of early cancers and high-grade dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39][40] Quantitative classification based on microendoscopy image texture features in Barrett's esophagus and esophageal squamous cell carcinoma, specifically gray-level co-occurrence matrices, has been previously investigated. [41][42][43] A recent publication on automated selection of high-quality frames in microendoscopic images 44 points to both the need for quality control, as well as the viability of automated extraction of high-quality frames during video-rate acquisition. Ongoing development work with microendoscopic systems may enable spectroscopic data to be used in conjunction with quantitative image features, such as those described in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous reports about optical noninvasive and/or less invasive methods for monitoring cancers, random surveillance biopsies are still the current gold standard for the identification of lesions. It was reported that the high-resolution microendoscope (HRME) developed by Richards-Kortum's group can be used to image and identify histopathologic features of metaplasia/ low grade dysplasia, high grade dysplasia, and esophageal adenocarinoma [17,18]. With the help of HRME, optical biopsies will be advanced into the in vivo clinical stage.…”
Section: Determination Of Dye-igg Conjugation Internalization Usinmentioning
confidence: 99%